2022
DOI: 10.1039/d2cp03484k
|View full text |Cite
|
Sign up to set email alerts
|

Design of need-based phosphors and scintillators by compositional modulation in the ZnGa2−xAlxO4:Cr3+ spinel: pure compound versus solid solutions

Abstract: Material which can depicts persistent near infrared (NIR) light under both ultraviolet (UV) and x-ray illumination can be boon to sustainable economy particularly for applications like optical imaging, solid state...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Similar observations were found in the average positron lifetimes in Cr-doped solid solutions of ZnGa 2 O 4 and ZnAl 2 O 4 . 33 The average positron lifetime in the undoped samples is smaller than in the Er and Yb doped samples in all cases. The doping increased the average lifetime significantly in Al rich samples compared to the Ga rich samples.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Similar observations were found in the average positron lifetimes in Cr-doped solid solutions of ZnGa 2 O 4 and ZnAl 2 O 4 . 33 The average positron lifetime in the undoped samples is smaller than in the Er and Yb doped samples in all cases. The doping increased the average lifetime significantly in Al rich samples compared to the Ga rich samples.…”
Section: Resultsmentioning
confidence: 79%
“…2(a) that t 1 is nearly constant in all the cases but the fraction of positrons annihilating with this lifetime gradually decreases (I 1 in Fig. 2 33 The average positron lifetime in the undoped samples is smaller than in the Er and Yb doped samples in all cases. The doping increased the average lifetime significantly in Al rich samples compared to the Ga rich samples.…”
Section: Positron Annihilation Lifetime Spectroscopymentioning
confidence: 89%
See 1 more Smart Citation
“…3,4 Also, aliovalent doping and high-temperature treatment result in an abundance of defects, which have a profound influence on the various functionalities of materials. 5,6 Most of the lanthanides are stable in the +3 oxidation state, though some display +2 and +4 oxidation states (Eu 2+ , Sm 2+ , Yb 2+ and Tb 4+ ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Byun et al reported blue, green, and red emission from undoped, Tb-doped, and Eu-doped ZnGa 2 O 4 , respectively . Cr-doped ZnGa 2 O 4, which is a red phosphorescence material, has been extensively studied because of its potentiality toward in vivo imaging. Various efforts have been reported to improve the red long-lasting phosphorescence of Cr-doped ZnGa 2 O 4 by codoping with one or multiple elements. Mn-doped ZnGa 2 O 4 has also attracted the attention of various groups due to its broadband emission varying from green to deep red. , Recently, Chen et al showed that visible to near-infrared photoluminescence of Mn-doped ZnGa 2 O 4 can be achieved by manipulating the valence of Mn . Castaing et al reported that ZnGa 2 O 4 can be used for optical memory applications after doping with Ni .…”
Section: Introductionmentioning
confidence: 99%